Volumetric Object Reconstruction in Multi-Camera Scenarios - Hernández Murillo, Enrique; López Nicolás, Gonzalo; Aragüés, Rosario (Jornada de Jóvenes Investigadores del I3A, 2019)
Volumetric reconstruction of unknown objects is essential in robotic manipulation. Building the 3D model requires a set of views so we consider a multi-camera scenario. We study an effective configuration strategy to address camera constraints such as the limited field of view or self-occlusions.